Transient thermal analysis of standard planetary roller screw mechanism based on finite element method. (December 2018) - Du, Chuanming; Liu, Geng; Qiao, Guan; Ma, Shangjun; Cai, Wei
The thermal behavior of the standard planetary roller screw mechanism needs to be investigated since the large amount of heat generated by the friction torque on multiple contact points during the transmission process. In this article, a simplified transmission system model of standard planetary roller screw mechanism is first established for the finite element analysis. Second, the friction torque of standard planetary roller screw mechanism is calculated and the boundary conditions of thermal analysis are deduced. Then, the transient thermal analysis of the standard planetary roller screw mechanism based on finite element method is conducted by considering the moving heat source and thus temperature field distribution at any time and the temperature rise curve at different positions of the standard planetary roller screw mechanism can be obtained. Finally, the correlation between the experimental data and the calculated values confirms the validity of the proposed thermal model for the transient thermal analysis.